Coping strategies of nurses in the care of patients with head and neck neoplasms - Naira Agostini Rodrigues dos Santos; Antonio Tadeu Cheriff dos Santos; Rildo Pereira da Silva
Abstract OBJECTIVE To understand and describe the experience of the development of coping strategies during the professional life of nurses providing care to patients with facial image alteration. METHOD Descriptive qualitative study with a hermeneutic-dialectic framework conducted in the head and neck ward of a reference hospital in Rio de Janeiro, with the participation of eight nurses and data produced through semi-structured interviews conducted between June and August 2013. RESULTS Three major impressions were found: initial estrangement and complexity, consisting in the care given to patients with facial image alteration; a threshold between estrangement and coping, corresponding to the emergence of coping strategies during care; and image-likeness as a (re)cognition of the individual with facial image alteration in the development and consolidation of coping strategies during care. CONCLUSION Among other contributions, the identification and understanding of coping strategies may contribute to better qualify nursing education and care.